Air Damping Analysis in Comb Microaccelerometer. (7th April 2014) - Zhou, Wu; Chen, Yu; Peng, Bei; Yang, Hui; Yu, Huijun; Liu, Heng; He, Xiaoping
Abstract : Air damping significantly influences the dynamical characteristics of MEMS accelerometers. Its effects at micro-scale level sharply depend on the structure layouts and size of MEMS devices. The damping phenomenon of comb microaccelerometers is investigated. The air between fixed plate electrodes and movable plate electrodes cannot flow freely and is compressed. The air damping, therefore, exhibits both viscous effects and stiffness effects. The former generates a drag force like that in macromechanical systems, and the damping force is proportional to the velocity of movable electrodes. The latter stiffens the rigidity of structure, and the stiffening level is related to the gap value of capacitors, internal pressure, and temperature. This paper focuses on the dependence of the squeeze film air damping on capacitor gaps. The simulation and experiments indicate that the squeeze film effect is sharply affected by the gap value when the structural dimensions decrease. And the influence of fabrication errors is considered in damping design in comb microaccelerometers.